Effectiveness of Maitland Mobilization Technique in Comparison with Mulligan Mobilization Technique in Management of Frozen Shoulder - Mamoona Anwar, Muhammad Waqas Mughal, Nabira Izhar, Maryam Rasheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Frozen shoulder refers to a common shoulder condition characterized by a general limitation of shoulder range of motion in the capsule model. The capsular pattern of the shoulder is characterized by the greatest limitation of passive lateral rotation and abduction. Physiotherapy is the most important part of the conservative treatment of frozen shoulder. Aim: To find the role of Maitland mobilization technique in treatment of frozen shoulder with Mulligan’s mobilization techniques and its possible effects in early gaining of ROM and pain management. Methods: This was a comparative study conducted at the Department of Physical Therapy and Orthopedic Surgery I, King Edward Medical College/Mayo Hospital, Lahore. Subjects were conveniently divided into her two groups, each group containing her 40 patients. In group A, patients were treated with Maitland manipulative therapy. In group B, patients were treated with mulligan mobilization and movement techniques. Patients in both groups were followed for up to 6 weeks and improvements in motor parameters were recorded at each patient's follow-up visit. SPSS was used for data entry and analysis. Result: A total of 50 patients participated in this study. The mean age of patients in group A was 46.23 years and the mean age of group B was 45.23 years at the onset of the disease at 6 weeks, 11 patients at 10 weeks, and 2 patients at 12-year intervals. Patients had an onset duration of 6 weeks, 10 patients had an onset duration of 10 weeks, and 6 patients had an onset duration of 12 weeks. Abduction was observed to be significantly improved in patients treated with the Mulligan method compared with those treated with the Maitland mobilization method. Practical implication: More specifically, the study will be focused on the examining the shoulder active and passive ROMs and pain reduction before and after the treatment. All measured characteristics of FS patients will be compared with those of the subjects with asymptomatic shoulders. Conclusion: In comparison with Mulligan mobilization technique, Maitland mobilization technique is more effective in the management of frozen shoulder. Keywords: Adhesive capsulitis /Frozen shoulder, Mulligan mobilization technique, Maitland mobilization technique.